2021
DOI: 10.17721/moca.2021.103-111
|View full text |Cite
|
Sign up to set email alerts
|

Voltammetric Determination of Paracetamol in Pharmaceutical Formulations at Iodine-Coated Polycrystalline Platinum Electrode

Abstract: In this work the modified iodine-coated polycrystalline platinum electrode was used to develope a voltammetric sensor for paracetamol determination in pharmaceutical formulations. The optimized experimental parameters for the determination of paracetamol were using 0.5 M H2SO4 as a supporting electrolyte with a scan rate of 50 mV/s. The anodic peak related to paracetamol oxidation was centered at about +0.60 V. The extended calibration graph was constructed between 1 ppm and 500 ppm. The anodic current showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…Given its significance, numerous researchers have focused on analyzing this drug in its different forms, including tablets, syrups, and injections. Methods employed for estimating paracetamol concentrations include high-performance liquid chromatography [4][5][6], We observe that numerous researchers have heavily relied on optical spectroscopic methods for the quantitative estimation of various drugs [7], including those currently under investigation; flow injection analysis [8], first derivative spectroscopy [9,10], UV-visible spectroscopy [11,12], and electrochemical techniques [13,14]. Figure 1 illustrates the chemical structure of paracetamol.…”
Section: Introductionmentioning
confidence: 99%
“…Given its significance, numerous researchers have focused on analyzing this drug in its different forms, including tablets, syrups, and injections. Methods employed for estimating paracetamol concentrations include high-performance liquid chromatography [4][5][6], We observe that numerous researchers have heavily relied on optical spectroscopic methods for the quantitative estimation of various drugs [7], including those currently under investigation; flow injection analysis [8], first derivative spectroscopy [9,10], UV-visible spectroscopy [11,12], and electrochemical techniques [13,14]. Figure 1 illustrates the chemical structure of paracetamol.…”
Section: Introductionmentioning
confidence: 99%
“…Most voltammetric techniques rely on the use of modified carbon based electrodes such as; a multiwalled carbon nanotube on pyrolytic graphite electrode (Kachoosangi et al, 2008), Fe (III) doped zeolite-graphite composite (Amare, 2019), Bi 2 O 3 nanoparticles modified GCE (Zidan et al, 2011), MOF-199 based electrode (Minh et al, 2018), graphene based electrode (Kang et al, 2010), graphitic carbon nitrideelectrochemically deposited-poly(3,4-ethylenedioxythiophene) (g-C3N4-E-PEDOT) composite electrode (Xu et al, 2018), graphite oxide film modified electrode (Song et al, 2011), multiwalled carbon nanotubes decorated with Bi (III) oxide electrode (Chipeture et al, 2019), a nanohybrid of palladium-reduced graphene oxide modified with gold nanoparticle electrode (Wang et al, 2018) and platinum nitrogen-doped graphene nanocomposite (Anuar et al, 2018). Recently, (Amayreh et al, 2021;Kassem et al, 2022) reported the voltammetry determination of PCT using modified iodine-coated polycrystalline platinum electrode and the use of Cu-nanoparticles on glassy carbon electrode. In the present work, we report the application of glycine modified carbon paste electrodes (GlyCPE) for the sensitive detection of PCT in tablet formulation using cyclic voltammetric and differential pulse stripping voltammetric techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Hemoglobin, which is an iron containing-protein in the blood, has long been used as an indicator to certify the safety and quality of blood prior to donation 155,156 .…”
Section: Introductionmentioning
confidence: 99%